Global warming and heat wave risks for cardiovascular diseases: A position paper from the Portuguese Society of Cardiology - Caldeira, Daniel (2023)
Global warming is a result of the increased emission of greenhouse gases. The consequences of this climate change threaten society, biodiversity, food and resource availability. The consequences include an increased risk of cardiovascular (CV) disease and cardiovascular mortality. In this position paper, we summarize the data from the main studies that assess the risks of a temperature increase or heat waves in CV events (CV mortality, myocardial infarction, heart failure, stroke, and CV hospitalizations), as well as the data concerning air pollution as an enhancer of temperature-related CV risks. The data currently support global warming/heat waves (extreme temperatures) as cardiovascular threats. Achieving neutrality in emissions to prevent global warming is essential and it is likely to have an effect in the global health, including the cardiovascular health. Simultaneously, urgent steps are required to adapt the society and individuals to this new climatic context that is potentially harmful for cardiovascular health. Multidisciplinary teams should plan and intervene healthcare related to temperature changes and heat waves and advocate for a change in environmental health policy.